Polyamine Inhibitors for Treatment of Feline Oral Squamous Cell Carcinoma: A Proof-of-Concept Study. (September 2013) - Lewis, John R.; O'Brien, Thomas G.; Skorupski, Katherine A.; Krick, Erika L.; Reiter, Alexander M.; Jennings, Michael W.; Jurney, Carrie H.; Shofer, FS; Sorenmo, Karin U.
This study assessed proof-of-concept for use of polyamine inhibitor 2-difluoromethylornithine (DFMO) as a treatment for oral squamous cell carcinoma (SCC) in client-owned cats. Polyamine levels in tumor tissue and normal oral mucosa were quantified before and after treatment. DFMO was administered orally to 14 client-owned cats with histologically confirmed oral SCC. Patients were monitored for gastrointestinal, dermatologic, auditory, hematological, and biochemical abnormalities. Total polyamine levels in tumor tissue decreased after treatment, as did the specific polyamine putrescine in both tumor tissue and normal mucosa. Ototoxicity was observed in 5 of 6 cats receiving pre- and post-treatment brainstem auditory evoked potential tests. Subclinical thrombocytopenia was observed in 6 of 14 cats. One cat showed mild post-anesthetic tremors that resolved without treatment. Oral administration of DFMO at doses used in this study resulted in significantly decreased tumor polyamine levels without life-threatening clinical or hema-tological toxicities. Further studies are warranted to explore pathophysiology of polyamine biochemistry and use of polyamine inhibitors in treatment of cats with oral SCC.